Cross sectional determinants of VO2 max in free living Iranians: Potential role of metabolic syndrome components and vitamin D status. Issue 7 (July 2022) - Babaei, Nadia; Davarzani, Samira; Motlagh, Sheida; Ebaditabar, Mojdeh; Saeidifard, Nasim; Mohammadi-Farsani, Gholamreza; Djafarian, Kurosh; Soares, Mario J.; Shab-Bidar, Sakineh
Abstract: Background and aims: The purpose of the study was to evaluate the determinants of cardiorespiratory fitness (CRF) in Iranian adults and the potential contribution of vitamin D status. Methods: In this cross-sectional study 264 cases (116 men and 147 women aged 18–70 years old were participated. Maximal oxygen consumption (VO2 max ) was measured by the Bruce protocol utilizing treadmill exercise testing. Anthropometric data, body composition and fasting blood glucose and lipid concentrations were measured. Serum levels of 25-hydroxyvitamin D (25(OH)D) and 1, 25-dihydroxyvitamin D (1, 25(OH)2 D) were assessed using enzyme-linked immunosorbent assay. Stepwise linear regression analysis was applied to determine significant predictors of VO2 peak. We tested non-linear (quadratic and cubic terms) versus linear association of adjusted (for determinants) VO2 max and vitamin D levels. Results: Multiple regression results showed that fat free mass, HDL-C and physical activity, waist circumference, age and sex were determinants of VO2 peak . All of these explained the 65.3% of VO2 peak. There was a non-linear cubic association (R 2 = 0.03, p = 0.046) between serum 25(OH)D and adjusted VO2 peak in which 25(OH)D in people with a high 25(OH)D levels (>60 nmol/L), had better fitness and those with serum 25(OH) less than 20 nmol/L. We found no linear and non-linear associations between serum 1, 25(OH)2 D and adjusted VO2 max . Conclusions: Our results showed that waist circumference and HDL-C, as components of metabolic syndrome, contribute ∼2% to the variance in VO2 max . Moreover, high concentrations of 25(OH)D but not 1, 25(OH)2 D may make additional contributions to CRF. Highlights: Cardiorespiratory fitness may be associated with metabolic syndrome and low levels of serum vitamin D. Waist circumference and high density lipoprotein cholesterol were determinants of cardiorespiratory fitness. High concentrations of 25(OH)D may be associated with a better cardiorespiratory fitness. Nor linear and neither non-linear associations were found between 1, 25(OH)2 D and cardiorespiratory fitness.